HISTORICAL AND CULTURAL APPROACH IN THE TRAINING OF FUTURE SPECIALISTS - Коляда, Наталія; Левченко, Наталія (Modern engineering and innovative technologies, 2023)
The article reveals the importance of the historical and cultural approach in the training of future specialists. The authors analyzed the experience of the scientific research center of pedagogical regional studies operating at the Uman State Pedagogical